2021
DOI: 10.1002/tpg2.20174
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study for lignocellulosic compounds and fermentable sugar in rice straw

Abstract: Cellulose and lignin are the two main components of secondary plant cell walls with substantial impact on stalk in the field and on straw during industrial processing. The amount of fermentable sugar that can be accessed is another important parameter affecting various industrial applications. In the present study, genetic variability of rice (Oryza sativa L.) genotypes for cellulose, lignin, and fermentable sugars contents was analyzed in rice straw. A genome‐wide association study of 33,484 single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…The studied plant panel consisted of 197 rice accessions collected from 70 countries (Supplemental Table S1). The grains from these accessions were previously analyzed in another GWAS project to understand the genetic control of starch and (1,3;1,4)‐β‐glucan content in grain (Panahabadi et al., 2021) and cellulose, lignin, and fermentable sugars in rice straw (Panahabadi et al., 2022). Our new analyses present major monosaccharides composition (including arabinose, xylose, mannose, galactose, fucose, and rhamnose) in whole grain of the same accessions.…”
Section: Resultsmentioning
confidence: 99%
“…The studied plant panel consisted of 197 rice accessions collected from 70 countries (Supplemental Table S1). The grains from these accessions were previously analyzed in another GWAS project to understand the genetic control of starch and (1,3;1,4)‐β‐glucan content in grain (Panahabadi et al., 2021) and cellulose, lignin, and fermentable sugars in rice straw (Panahabadi et al., 2022). Our new analyses present major monosaccharides composition (including arabinose, xylose, mannose, galactose, fucose, and rhamnose) in whole grain of the same accessions.…”
Section: Resultsmentioning
confidence: 99%
“…PtrLAC12 is a kind of laccase from poplar; it is well known that laccase can participate in the synthesis and degradation of lignin in the xylem, and it is also directly related to the formation and modification of the cell wall (W. Bao et al., 1993; LaFayette et al., 1999; Y. Liu et al., 2020; Sharma et al., 2020). AtVLN2 belongs to the Villin family, members of this family are associated with SCW formation and thickening (Panahabadi et al., 2022). In studies of Arabidopsis , it was found that there was a significant reduction in the cell numbers in the cortex, inter‐fascicular fibers, xylem, and pith in vln2 vln3 double mutants, it means that AtVLN2 may involve in secondary xylem development (C. Bao et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Micro‐checker software was used to check scoring errors, stutter, or null alleles (Van Oosterhout et al, 2004 ). Gametic disequilibrium between all pairs of microsatellite loci was tested using POPGENE (Version: 1.32; Panahabadi et al, 2021 , 2022 ; Yeh Francis et al, 1999 ). Null alleles and deviations from Hardy–Weinberg equilibrium for each locus were estimated using Genepop (Version 4.2.1; Panhabadi et al, 2022 ; Rousset, 2008 ).…”
Section: Methodsmentioning
confidence: 99%